Wearable sensors for real-zime kinematics analysis in sports: A review - Rana, M.; Mittal, M. (IEEE Sensors Journal, 2021)
Wearable Inertial sensors have revolutionised the way kinematics analysis is performed in sports. This paper aims to present a comprehensive review of the literature related to the use of wearable inertial sensors for performance analysis in various games. Kinematics analysis using wearable sensors can provide real-time feedback to the players about their adopted techniques in their respective sports and thus help them to perform efficiently. This article reviews the key technologies (IMU sensors, communication technology, data fusion and data analysis techniques) that enable the implementation of wearable sensors for performance analysis in sports. The review focuses on research papers, commercial sports sensors and 3D motion tracking products to provide a holistic and systematic categorisation & analysis of the wearable sensors in sports. The review identifies the importance of sensors classification, applications and performance parameters in sports for structured analysis. The survey also reviews the technology concerning sensor architecture, network and communication protocols, covers various data fusion algorithms and their accuracy while throwing light on essential performance matrices for an athlete. This review paper will assist both end-users and the researchers to have a comprehensive glimpse of the wearable technology pertaining to designing sensors and solutions for athletes in different sports.